2005
DOI: 10.1111/j.1365-2559.2005.02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe gastritis in the Peruvian Andes

Abstract: This study suggests that the severity of H. pylori-associated gastric lesions seen on histopathological examination is greater in patients living at high altitude, the cause of which is most probably multifactorial but nonetheless principally altitude related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Previous studies from Peru have shown that ChAG is found predominantly in the antrum region and is more severe than ChAG that is found in the body of the stomach 31–33. In the present study, we also found ChAG to occur more frequently in the antrum region, and only in this gastric site was an association between ChAG and the C allele statistically significant.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies from Peru have shown that ChAG is found predominantly in the antrum region and is more severe than ChAG that is found in the body of the stomach 31–33. In the present study, we also found ChAG to occur more frequently in the antrum region, and only in this gastric site was an association between ChAG and the C allele statistically significant.…”
Section: Discussionsupporting
confidence: 74%
“…In Ecuador, the ASMRs are 28.0 for males and 24.1 for females, and in Peru 22.6 for males and 19.5 for females. A study in Peru found that patients in La Oroya City, located at 3700 m in altitude, presented more severe gastric lesions, including atrophic gastritis and intestinal metaplasia in body and antrum than patients from Lima, at the sea level [18] further documenting higher risk for gastric cancer in mountainous regions. In Bolivia, the ASMRs are 15.1 for males and 13 for females, these lower rates potentially reflecting the transition to the Altiplano desert between Bolivia and Chile (Fig.…”
Section: Is Gastric Cancer Associated With Altitude In Latin America?mentioning
confidence: 99%
“…The exposure to high altitude hypoxia causes severe damage to different organs, especially the intestinal tract. There is increasing experimental evidence suggesting that hypoxia induced inflammation in the gastrointestinal tract [1,2,3]. Hypoxia may induce severe primary intestinal barrier dysfunction, promote bacterial and endotoxic translocation, and cause systemic inflammatory response; it is the major factor causing high-altitude multiple organ dysfunction syndromes [4].…”
Section: Introductionmentioning
confidence: 99%